PEMELIHARAAN RUTIN LINGKAR KOTA GORONTALO GORR SEGMEN II (SWAKELOLA) - Nurhediyati Tome; Ronny Bumulo; Vannyarti Yasin; Rahmat R. Habibie (Jurnal Pengabdian kepada Masyarakat (J-PMas), 2022)
The GORR construction road is one of the non-toll (unpaid) national roads carried out by the Gorontalo National Road Implementation Agency (BPJN) in stages since 2014, divided into 3 segments. The existence of this ring road is also an alternative route for vehicles to Gorontalo Harbor as a collection port. With this community service, it is hoped that it can provide a useful overview of the relationship between studying in the civil engineering department and a work environment that is full of dynamics, starting from understanding the maintenance of a construction to the implementation process in the field, both in terms of the processes that occur or work mechanisms, management. operation and technical quality control as well as being able to analyze behaviors or problems that often occur.